Chapeau de gendarme in a toddler points to focal epilepsy originating from the subcentral gyrus. Issue 2 (15th June 2021) - Rüsch, Christina T.; Bölsterli, Bigna K.; Carosio, Carlotta; Ramantani, Georgia
Abstract: The chapeau de gendarme sign or ictal pouting has been associated with focal epilepsy of frontal origin. The identification and characterization of this semiologic feature derive mainly from adult epilepsy surgery series, whereas paediatric cases have rarely been reported. Here, we present a 14‐month‐old girl with a chapeau de gendarme sign with eyes closed as the sole initial manifestation of left frontal lobe epilepsy. Brain MRI revealed an area suspicious for focal cortical dysplasia in the anterior aspect of the left subcentral gyrus, and ictal scalp EEG supported a seizure onset correlating with the lesion. This is the youngest reported patient with a chapeau de gendarme sign and the first to be associated with a lesion in the subcentral gyrus. Our observation extends the age range of patients presenting with this intriguing semiology and the range of localizations where it may originate. We propose considering the chapeau de gendarme sign as a hallmark of focal epilepsy in all age groups, including early life, and that presurgical evaluation should be timely initiated in patients with refractory seizures. [ Published with video sequence ].